Evaluating frailty scores to predict mortality in older adults using data from population based electronic health records: case control study. (13th March 2018) - Stow, Daniel; Matthews, Fiona E; Barclay, Stephen; Iliffe, Steve; Clegg, Andrew; De Biase, Sarah; Robinson, Louise; Hanratty, Barbara
Abstract: Background: recognising that a patient is nearing the end of life is essential, to enable professional carers to discuss prognosis and preferences for end of life care. Objective: investigate whether an electronic frailty index (eFI) generated from routinely collected data, can be used to predict mortality at an individual level. Design: historical prospective case control study. Setting: UK primary care electronic health records. Subjects: 13, 149 individuals age 75 and over who died between 01/01/2015 and 01/01/2016, 1:1 matched by age and sex to individuals with no record of death in the same time period. Methods: two subsamples were randomly selected to enable development and validation of the association between eFI 3 months prior to death and mortality. Receiver operator characteristic (ROC) analyses were used to examine diagnostic accuracy of eFI at 3 months prior to death. Results: an eFI > 0.19 predicted mortality in the development sample at 75% sensitivity and 69% area under received operating curve (AUC). In the validation dataset this cut point gave 76% sensitivity, 53% specificity. Conclusions: the eFI measured at a single time point has low predictive value for individual risk of death, even 3 months prior to death. Although the eFI is a strong predictor or mortality at a population level, its use for individuals is far less clear